METODE TAMYIZ TERHADAP KEMAMPUAN SANTRI DALAM MENTERJEMAHKAN Al-QUR’AN - Dewi Nurfitriani, Oking Setia Priyatna, Suhendra (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2020)
Studying the Qur'an is very important but today, it seems to be a big challenge, because more and more people are reluctant to study the Qur'an and learn to translate it, even though it is clear that the Qur'an is a source the principal teachings of Islam, which we should as Muslims are obliged to learn. The method is an important thing in the learning process, one of the methods is the tamyiz method, which is a method used specifically for learning to translate the Qur'an and the yellow book. This makes the tamyiz method as a method that is quite capable of accommodating the needs of students in the process of translating the Qur'an. The purpose of this study is 1). To find out how the effect of the application of the Tamyiz method on the ability of students to translate the Qur'an at the Al-Karimah Islamic Boarding School in Sukaraja, Bogor. The research method used in this study is an experimental research method. The results of the study stated that there was a significant influence between the tamyiz method on the ability of students to translate the Qur'an in the Al-Karimah Islamic Boarding School in Sukaraja, Bogor. This is known based on hypothesis testing with a sample size of 50 students at Al-Karimah Islamic Boarding School in Sukaraja Bogor, from the data obtained 0.828 results. Thus, the application of the tamyiz method in Al-Karimah Sukaraja Islamic Boarding School was proven to be able to improve the ability of students to translate the Qur'an. This was obtained from the results of data analysis from questionnaire values ​​and pre-test post-tests that have been conducted by researchers.